Dinamika Komunikasi Antargenerasi Pegawai Gen Z dan Milenial di PT Inalum : Studi Kasus Komunikasi Antargenerasi Pegawai Gen Z dan Milenial di PT Inalum - Garneta Asmarandhini Putri Kusnandar; Kismiyati El Karimah; Yuliani Dewi Risanti Sunarya (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aimed to analyze intergenerational communication dynamics, particularly between Generation Z and Millennials, in the workplace of PT Indonesia Asahan Aluminium (PT Inalum). Differences in generational characteristics created challenges in organizational communication, thus requiring an understanding of interaction patterns and adaptive strategies. This study used a qualitative approach with a descriptive method. Data were collected through in-depth interviews, moderate participant observation, and documentation. The informants consisted of Generation Z and Millennial employees, as well as key informants from Generation X. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results showed that differences in communication styles were influenced by work experience, mindset, and communication preferences. Generation Z tended to be more open, fast, and technology-oriented, while Millennials demonstrated a more adaptive and contextual approach. Intergenerational communication involved accommodation strategies through adjustments in communication styles to achieve effective interaction. The organizational environment also played a role in shaping communication patterns and reducing potential conflicts. This study highlights the importance of adaptive communication strategies in supporting work effectiveness and relationships among employees from different generations.